EFEKTIVITAS AERASI, SEDIMENTASI, DAN FILTRASI UNTUK MENURUNKAN KEKERUHAN DAN KADAR BESI (Fe) DALAM AIR - Febiary, Irfan; Widiyanto, Agnes Fitria; Yuniarno, Saudin (Kesmas Indonesia: Jurnal Ilmiah Kesehatan Masyarakat, 2016)
Water is an essential material in live. Water with high level of turbidity and iron can lead to health problems. Water treatment can be done by aerasi sistem tray, sedimentation and filtration. The aim of this study was to know the effectiveness of aerasi sistem tray, sedimentation and filtration on reducing turbidity and iron level in water. This study was a quasy experiment with post test only with control group design. The methods are treatment with aerasi tray system, sedimentation, filtration, aerasi tray system-sedimentation, aerasi tray system-filtration, sedimentation-filtration, and aerasi tray system-sedimentation-filtration. The study has been conducted in Fishery and Marine Departement Laboratory UNSOED and iron level test has beed conducted in Health Laboratory o Purbalingga. The result showed treatment of aerasi tray system-sedimentation-filtration efektif toreduce turbidity and iron level in groundwater. The society can apply the aerator, sedimentation and filtration methods to reduce turbidity and iron level in groundwater